A isenção tributária de IPTU e o custo para sociedade de Fortaleza - Maia Filho, Zuilton de Mendonça (2020)
This work analyzed the impacts on taxes in the Municipality of Fortaleza – CE related to the concessions of tax exemptions collected by the municipality, more specifically the Tax on Urban Property and Territorial Property (IPTU). When analyzing the tax exemption of the Municipality of Fortaleza, based on tax exemptions from IPTU, in the modalities contained in the Municipal Tax Code of Fortaleza, it was clear that there was a concentration of exemption in the city's most upscale neighborhoods, based on the granting of exemption for municipal public servants, concentrated in the Regional Executive Secretariat II. The incidence of taxes must take into account the contributory capacity, determined by the economic condition of the citizen and, not only, due to the fact that these properties belong to public servants, there is no plausible justification for avoiding the payment of such a tax because they hold a position public. At the other extreme, in other regions where neighborhoods with lower purchasing power are concentrated, there is a higher incidence of exemption due to the property's market value. Finally, it can be said that when public resources are distributed more equitably, it will favor the development of the population of the Municipality of Fortaleza.